Trends in Brazilian scientific production about moral distress in health professionals (Research, Society and Development, 2021)
The objective is to identify and characterize trends in Brazilian theses and dissertations about moral distress in health professionals. This is a narrative review carried out in the Theses and Dissertations Catalog of the Coordination for the Improvement of Personnel Higher Education. The bibliographic search took place in December 2020. The terms "moral distress" OR " distress moral" were defined as the search strategy. Were retrieved 66 studies and, based on the reading of titles and abstracts, 22 productions were included for analysis. Of these, eight were theses and 14 were dissertations. The results were presented in two categories of analysis: Characterization of theses and dissertations on moral distress in health professionals; and trends on issues related to moral distress in health professionals. The following contributing factors to the occurrence of moral distress were identified: insufficient work conditions, insufficiency of human and material resources, work overload and lack of competence of the work team, in addition to negative physical and/or emotional repercussions that can generate in health professionals; the nursing team was the health professionals who covered most of the studies. It is noticed that this theme is being investigated in different scenarios of action, with the predominant presence of the nursing public, which highlights a knowledge gap and encourages the development of new studies with health professionals in the multidisciplinary scope.